Bioluminescence imaging of fibroblast activation protein-alpha in vivo and human plasma with highly sensitive probe - Zhang, Ling; Ying, Weiwu; Sheng, Zhijia; Lv, Li; Gao, Jian; Xue, Yunsheng; Liu, Ling (Analytical biochemistry, 2022)
Fibroblast activation protein-alpha (FAPα) has emerged as a biomarker of tumor stromal fibroblasts. FAP was overexpressed in stromal fibroblasts of human malignancies and positively correlated with the depth of tumor invasion, lymphatic metastasis, distant metastases, high TNM stage and poor prognosis. However, the circulating FAP levels in the plasma of gastric cancer patients and the relationship between FAP levels and gastric cancer remain unknown. Moreover, probes with super selectivity, extremely high sensitivity, and excellent performance in quantitative detection are still lacking. Herein, we developed the bioluminescent probe BL-FAP for sensitive detection and imaging of endogenous FAP in gastric cancer cells and tissues and plasma from gastric cancer patients. The probe exhibited the high signal-to-noise ratio (15000∼fold), the excellent selectivity (FAP/DPP IV ratio and FAP/PREP ratio = 50000∼ fold), and the high sensitivity (18.1 pg/mL). BL-FAP facilitates monitoring of endogenous FAP in living cells and nude mice bearing MGC-803-luc tumors. More importantly, this probe was successfully applied to the measurement of FAP activity levels in plasma from gastric cancer patients for the first time. A significant enhancement in FAP levels was observed in patients with gastric cancer, suggesting that the FAP level may be a potential diagnostic parameter for gastric cancer. [Display omitted] •A novel bioluminescent probe for highly sensitive detection of FAP was reported.•This probe exhibited the best selectivity, and the highest sensitivity (18.1 pg/mL).•This probe exhibited the highest signal-to-noise ratio (15000∼fold).•Quantitative measurement of FAP activity levels in plasma from gastric cancer patients for the first time.